sin theta/ sin theta - cos theta
= (convert to)
sin theta (sin theta - cos theta)/ 1 - 2 sin theta cos theta
how should i start this?
pls.. help
ok tnks.. haha..
by the way is this right?
= sin theta (sin theta - cos theta)/ (sin theta - cos theta)(sin theta - cos theta)
= sin theta (sin theta - cos theta)/ sin^2 theta - sin theta cos theta - cos theta sin theta + cos^2 theta
(sin^2 theta + cos^2 theta = 1)
(- sin theta cos theta - cos theta sin theta= -2 sin theta cos theta)
= sin theta (sin theta - cos theta)/ 1-2 sin theta cos theta